The Visualization System of CAD Drawing Workpiece - Nayonglin; Liu, Shugui; Zhang, Guoxiong; Ma, Xinhui (COMPUTER SIMULATION, 2003)
This paper presents a visualization system that can complete the visualization process of CAD drawing workpieces. It introduces the four main functional modules of the visualization system: IGES file extraction and recognition, 3D reconstruction, graphics model creation and optimization, and visualization module. And gave a specific experiment.